Search for new phenomena in final states with large jet multiplicities and missing transverse momentum at s√=8 TeV proton-proton collisions using the ATLAS experiment - Onofre, A. (2013)
A search is presented for new particles decaying to large numbers (7 or more) of jets, with missing transverse momentum and no isolated electrons or muons. This analysis uses 20.3 fb−1 of pp collision data at √ s = 8 TeV collected by the ATLAS experiment at the Large Hadron Collider. The sensitivity of the search is enhanced by considering the number of b-tagged jets and the scalar sum of masses of large-radius jets in an event. No evidence is found for physics beyond the Standard Model. The results are interpreted in the context of various simplified supersymmetry-inspired models where gluinos are pair produced, as well as an mSUGRA/CMSSM model.